2018
DOI: 10.1016/j.jadohealth.2017.11.306
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Fertility and Reproductive Health Among Transgender and Gender-Nonconforming Adolescents

Abstract: TGNC adolescents expressed interest in multiple family building options, including adoption and biological parenthood, and identified a need for more information about these options. Thus, clinicians working with adolescents should be aware of the unique fertility and reproductive health needs of TGNC youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 30 publications
2
97
0
1
Order By: Relevance
“…Prior studies indicate it is relatively rare for transgender youth to opt for fertility preservation interventions. 66,67 Although reasons for this reluctance are not entirely clear, a number of barriers exist, 11,69 including developmental (age), cognitive (focus on establishing gender identity), structural (cost, invasiveness), and provider (knowledge, resources) challenges. Ethical concerns centering on the principles of autonomy (parent/ child decisional conflict about hormonal therapies and fertility preservation) and justice (inability to access fertility preservation treatments because of due to cost) are common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies indicate it is relatively rare for transgender youth to opt for fertility preservation interventions. 66,67 Although reasons for this reluctance are not entirely clear, a number of barriers exist, 11,69 including developmental (age), cognitive (focus on establishing gender identity), structural (cost, invasiveness), and provider (knowledge, resources) challenges. Ethical concerns centering on the principles of autonomy (parent/ child decisional conflict about hormonal therapies and fertility preservation) and justice (inability to access fertility preservation treatments because of due to cost) are common.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 60% of this sample were interested in learning more about their fertility options, which was consistent with qualitative reports pointing to the need for additional information about "fertility for people who are transitioning from one gender to another." 69 A validated questionnaire was recently developed to explore fertility-related attitudes among transgender adolescents and may be useful for future work in this area; efforts should be made in this future research to examine fertilityrelated perspectives of nonbinary or gender fluid adolescents as well. 68 It is also important to note that fertility desires are not the only consideration in making decisions about pursuing fertility preservation; risks of worsening gender dysphoria to pursue gamete cryopreservation is an important individual factor, as documented in a recent case report of 2 transmasculine adolescents who ultimately made different decisions about fertility preservation.…”
Section: February 2019mentioning
confidence: 99%
“…Only a few studies assessed fertility desires in transgender children and adolescents . To evaluate fertility desires in transgender children, a 15‐item instrument, the Transgender Youth Fertility Attitudes Questionnaire, has recently been developed.…”
Section: Methodsmentioning
confidence: 99%
“…In another study by Nahata et al, nearly half of the participants reported no desire to have biological children. A recent online survey conducted on a sample of 156 (age range 14‐17 years) gender nonconforming adolescents revealed that 36% of these individuals want to have biological children. Only 14% of the survey participants reported discussing the effects of hormonal treatment on fertility with their healthcare providers, and 61% expressed the need for more information about fertility‐related issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation